Lacrimal sac dacryolith (76 cases): a predictive factor for successful endonasal dacryocystorhinostomy? - Komínek, Pavel; Červenka, Stanislav; Zeleník, Karol; Pniak, Tomáš; Tomášková, Hana; Matoušek, Petr (European archives of oto-rhino-laryngology, 2014)
To evaluate whether the presence of dacryolith is a predictive factor for successful dacryocystorhinostomy. The success rate of endonasal dacryocystorhinostomy (EDCR) performed to relieve obstruction of the nasolacrimal duct was evaluated according to the presence of dacryolithiasis. The surgical results of patients with (group I) and without dacryoliths (group II) were analysed and compared 1-year post surgery. A total of 771 EDCRs performed from 1994 to 2010 were evaluated. Dacryolith was found in 76/771 procedures (9.9%). Complete improvement was achieved significantly more frequently in group I (76/76; 100.0%) than in group II (633/695; 91.1%; p < 0.001). EDCRs were performed significantly more frequently in people aged 31-50-years, the average age of the group I was 41.1 years (range 18-72 years), of the group II 53.3 years (range 3 months-86 years; p < 0.001). There was no significant difference in the female-to-male ratio in the two groups. The presence of dacryoliths is a predictive factor for successful endonasal dacryocystorhinostomy.
Keywords: mladý dospělý; předškolní dítě; retrospektivní studie; Child; senioři nad 80 let; dakryocystorinostomie; Humans; lidé; Retrospective Studies; mladiství; endoskopie; lidé středního věku; Lacrimal Duct Obstruction; Dacryocystorhinostomy; Middle Aged; Aged, 80 and over; Case-Control Studies; nemoci slzného ústrojí; Female; Male; Adult; prognóza; Prognosis; kojenec; mužské pohlaví; Cohort Studies; Aged; studie případů a kontrol; Infant; Lithiasis; litiáza; ženské pohlaví; Endoscopy; Lacrimal Apparatus Diseases; Child, Preschool; Young Adult; dospělí; kohortové studie; obstrukce slzovodu; dítě; Adolescent; senioři